Impact of classical homocystinuria on health care resource utilization and costs in the United States: A retrospective cohort study - Mahim Jain; Mehul Shah; Kamlesh M. Thakker; Andrew Rava; Agness Pelts Block; Colette Ndiba-Markey; Lionel Pinto (Molecular Genetics and Metabolism Reports)
Background and objectives: Classical homocystinuria (HCU) is a rare autosomal recessive disease that can affect multiple organ systems leading to increased health care resource utilization (HCRU) and costs. In this study, we aimed to utilize United States claims data to describe the all-cause HCRU and costs of HCU and to compare these when stratified by total homocysteine (tHcy) level. Methods: This was a retrospective cohort study using Optum's de-identified Market Clarity Data from January 01, 2016, through September 30, 2021. Patients were initially selected if they had at least 1 International Classification of Diseases, Tenth Revision diagnosis code for homocystinuria (E72.11) or homocystinuria signs, disease, and symptoms term in the Market Clarity Dataset. Patients were subsequently selected by using a multi-parameter algorithm encompassing clinical and phenotypic characteristics and tHcy levels. Patients were excluded if they had cancer, a COVID-19 hospitalization, or pregnancy. Unadjusted all-cause HCRU and costs (adjusted to 2021 United States dollars) per patient per month (PPPM) over the follow-up period were reported by health care setting using descriptive statistics. Unadjusted linear regression was used for comparisons across tHcy levels. Results: The overall study cohort included 143 eligible patients, 61 (42.7 %) had a tHcy level < 50 μM and 82 (57.3 %) had a tHcy level ≥ 50 μM. Within the subgroup with tHcy level ≥ 50 μM, 54 (65.9 %) had a tHcy level 50 to < 100 μM, and 28 (34.1 %) had a tHcy level ≥ 100 μM. In the overall cohort, 44.1 % of patients were female, mean age was 47.8 years, and most patients were White (76.9 %). Patients with higher tHcy levels had more unadjusted all-cause outpatient visits and pharmacy claims PPPM compared with those with lower tHcy levels. Mean total health care costs PPPM were $5139, $2722, and $925 in patients with tHcy ≥ 100 μM, 50 to < 100 μM, and < 50 μM, respectively (p < 0.001). Among patients with tHcy ≥ 100 μM, mean costs of pharmacy claims ($1886), inpatient admissions ($1611), and outpatient visits ($1523) contributed the most to the total health care costs and total, inpatient, outpatient, and pharmacy costs were all significantly higher in patients with higher tHcy levels (all p ≤ 0.01). Conclusions: All-cause HCRU and costs in patients with HCU were higher in patients with higher tHcy levels. A major portion of the costs were related to inpatient admissions, outpatient visits, and pharmacy claims. These results provide support for lowering tHcy levels through appropriate diet and treatment combination to reduce HCRU and the associated economic burden of HCU.